2007
DOI: 10.1038/sj.leu.2404961
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional dysregulation mediated by RUNX1-RUNX1T1 in normal human progenitor cells and in acute myeloid leukaemia

Abstract: The t(8;21)(q22;q22) occurs frequently in acute myelogenous leukaemia and gives rise to the transcription factor fusion protein, RUNX1-RUNX1T1 (also known as AML1-ETO). To identify the genes dysregulated by the aberrant transcriptional activity of RUNX1-RUNX1T1, we used microarrays to determine the effect of this mutation on gene expression in human progenitor cells and during subsequent development. Gene signatures of these developmental subsets were very dissimilar indicating that effects of RUNX1-RUNX1T1 ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
82
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(89 citation statements)
references
References 56 publications
5
82
2
Order By: Relevance
“…Lineage promiscuity in t(8;21) AML K Walter et al human CD34 þ cells showed neither PAX5 upregulation nor CD19 expression (Mulloy et al, 2005;Tonks et al, 2007). In addition, AML cells from conditional RUNX1/RUNX1T1 transgenic mice do not express CD19 (data not shown).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Lineage promiscuity in t(8;21) AML K Walter et al human CD34 þ cells showed neither PAX5 upregulation nor CD19 expression (Mulloy et al, 2005;Tonks et al, 2007). In addition, AML cells from conditional RUNX1/RUNX1T1 transgenic mice do not express CD19 (data not shown).…”
Section: Discussionmentioning
confidence: 90%
“…As a result, the RUNX1-RUNX1T1 fusion protein can recruit transcriptional co-repressor complexes to RUNX1 binding sites and thus represses RUNX1 target genes (Linggi et al, 2002;Follows et al, 2003). However, ectopic expression of RUNX1-RUNX1T1 in human CD34 þ hematopoietic precursor cells induces both the upregulation and downregulation of a number of genes (Mulloy et al, 2005;Tonks et al, 2007), indicating that the expression of this oncoprotein disturbs the entire myeloid gene regulatory network. This widespread dysregulation does not only affect myeloid-specific genes.…”
Section: Introductionmentioning
confidence: 99%
“…Expression of 1045 genes were dysregulated Ն 1.5-fold in AE9a LK cells, with 337 up-regulated and 486 down-regulated by at least 2-fold (P Ͻ .001, 2-sample t test; supplemental Table 1). Among these genes, 195 were also found to be dysregulated in AML1-ETO-transduced human hematopoietic cells [30][31][32] or t(8;21) AML blasts 33,34 (supplemental Table 2). Among the up-regulated genes are positive cell-cycle regulators, such as Ccnb1, Ccnd2, and Cdc25b.…”
Section: Gene Expression and Promoter Occupancy Profiling Of Primary mentioning
confidence: 99%
“…The following publicly available gene expression databases were used: http: //www.genecards.org, 56 http: //www.ebi.ac.uk/arrayexpress/ (for example, experiment E-MEXP-583) 57,58 and http://www.biogps.gnf.org.…”
Section: Online Resourcesmentioning
confidence: 99%